Association of Sociodemographic Factors and Maternal Educational Attainment with Child Development among Families Living below the Poverty Line in the State of Ceará, Northeastern Brazil - Hermano A. L. Rocha; Márcia M. T. Machado; Onélia M. M. L. de Santana; Sabrina G. M. O. Rocha; Camila M. de Aquino; Laécia G. A. Gomes; Lucas de S. Albuquerque; Maria D. de A. Soares; Álvaro J. M. Leite; Luciano L. Correia; Christopher R. Sudfeld (MDPI AG, 2023)
Maternal educational attainment has been identified as relevant to several child health and development outcomes. This study aimed to evaluate the association of sociodemographic and maternal education factors with child development in families living below the poverty line. A cross-sectional study was conducted through telephone contact from May to July 2021 in Ceará, a state in Northeastern Brazil. The study population comprised families with children up to six years of age participating in the cash transfer program "Mais infância". The families selected to participate in this program must have a monthly per capita income of less than US$16.50. The Ages and Stages Questionnaire version 3 was applied to assess the children's development status. The mothers reported maternal educational attainment as the highest grade and or degree obtained. The final weighted and adjusted model showed that maternal schooling was associated with the risk of delay in all domains except for the fine motor domain. The risk of delay in at least one domain was 2.5-fold higher in mothers with a lower level of schooling (95% CI: 1.6-3.9). The findings of this study suggest that mothers with higher educational attainment have children with better child development outcomes.